2013
DOI: 10.1016/j.brainres.2012.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Distinct neural correlates for pragmatic and semantic meaning processing: An event-related potential investigation of scalar implicature processing using picture-sentence verification

Abstract: The present study examines the brain-level representation and composition of meaning in scalar quantifiers (e.g., some), which have both a semantic meaning (at least one) and a pragmatic meaning (not all). We adopted a picture-sentence verification design to examine event-related potential (ERP) effects of reading infelicitous quantifiers for which the semantic meaning was correct with respect to the context but the pragmatic meaning was not, compared to quantifiers for which the semantic meaning was inconsist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
52
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 51 publications
11
52
4
Order By: Relevance
“…We note that such an account would still not provide direct evidence of processing cost associated with scalar inferencing–rather, it would suggest evidence of avoidance of inferencing entirely. It does not seem likely that inferences are only realized when a complement set is mentioned, given that inferences seem to be derived in sentences with no complement set (e.g., example (1b) in this article) and there is substantial experimental evidence for rapid and implicit sensitivity to inference-based meanings even in the absence of complement sets ([23], [24], among others). Moreover, anticipatory eye movements reflecting the realization of inferences have been observed following quantifiers, but before the mention of a contrast set or any subsequent referring expression [8], [25].…”
Section: Discussionmentioning
confidence: 86%
“…We note that such an account would still not provide direct evidence of processing cost associated with scalar inferencing–rather, it would suggest evidence of avoidance of inferencing entirely. It does not seem likely that inferences are only realized when a complement set is mentioned, given that inferences seem to be derived in sentences with no complement set (e.g., example (1b) in this article) and there is substantial experimental evidence for rapid and implicit sensitivity to inference-based meanings even in the absence of complement sets ([23], [24], among others). Moreover, anticipatory eye movements reflecting the realization of inferences have been observed following quantifiers, but before the mention of a contrast set or any subsequent referring expression [8], [25].…”
Section: Discussionmentioning
confidence: 86%
“…Two previous scalar implicature EEG studies observed negativities in relation to scalar implicature processing (Nieuwland et al, 2010; Politzer-Ahles et al, 2013). Though the distribution and onset of the negativities was different across the two studies, that could be due to the differences in methodology: Politzer-Ahles and colleagues (2013) involved sentence-picture matching whereas Nieuwland and colleagues (2010) used reading-only paradigm.…”
Section: Processing the Restmentioning
confidence: 78%
“…Though the distribution and onset of the negativities was different across the two studies, that could be due to the differences in methodology: Politzer-Ahles and colleagues (2013) involved sentence-picture matching whereas Nieuwland and colleagues (2010) used reading-only paradigm. The authors of both studies interpreted their effects as reflecting pragmatic activity related to scalar implicature processing, in which case one might have expected a similar effect in our study.…”
Section: Processing the Restmentioning
confidence: 93%
See 1 more Smart Citation
“…Comprehenders, for their part, must make sense of quantifiers along with reference and predication to arrive at an interpretation of the propositional content of, e.g., Most birds can fly . The project for theories of real-time language comprehension is to determine what quantifier interpretations are constructed and there is growing interest a variety of quantifier types: a selective sample of topics and reports includes investigations of bare cardinal quantifiers (e.g., Frazier, et al, 2005; Kaan, Dallas, & Barkley, 2007; Wijnen & Kaan, 2006); existential quantifiers and their scalar implicatures (e.g., Breheny, Katsos, & Williams, 2006; Huang & Snedeker, 2009; Politzer-Ahles, Fiorentino, Jiang, & Zhou, 2013); consequences of quantifier interpretations for discourse processing (e.g., Paterson, Filik, & Moxey, 2009; Sanford, Dawydiak, & Moxey, 2007); multiple quantification and scope ambiguities (e.g., Dwivedi, 2013; Filik, Paterson, & Liversedge, 2004; Kurtzman & Macdonald, 1993, and quantifiers and long-distance dependencies, e.g., Hackl, Koster-Hale, & Varvoutis, 2012). …”
Section: Introductionmentioning
confidence: 99%